Four important Documents about the History of Prekmurje in Early Modern Period - Hozjan, Andrej (Anali PAZU, 2022)
The presentation of four important documents about the history of Prekmurje in Early Modern Period includes four various historical sources. Each of them presents a part of local history of four most important market towns in Prekmurje in that period. The oldest pergament charter, that deals with the mentioned region of Eastern Slovenia, kept today in Slovenian archives, is a charter of privileges of a market town Turnišče from the year 1548, issued by its noble co-owners Ladislav (in Hung.: László) and Štefan (István) Banič (Bánffy) of Dolnja Lendava (Alsólendva; today: Lendava, SLO). The oldest yet known information about a concrete house or building in the market town of Dolnja Lendava is found in the paper charter from 1622, issued by count Krištof (Kristóf) Banič (Bánffy) of Dolnja Lendava, regarding his house, which was therefore given to a low nobleman Štefan (István) Falussy. The oldest yet known charter of an inhabitant of the market town of Murska Sobota is a paper charter from 1624, issued by a low nobleman Jurij (György) Péterffy for his wineyard. The oldest yet known list of inhabitants – house masters in the market towns of Prekmurje is a list of house masters in the market town of Gornja Lendava (Felső Lendva; today: Grad, SLO) from 1693.
Keywords: History of Prekmurje; Early Modern Period; Gornja Lendava; Murska Sobota; Turnišče; Dolnja Lendava